Pedagogic, Personality, Social, and Professional Competence Influences on Elementary Students’ Social Studies Interest - Kurnianti Kurnianti; Elpisah Elpisah; Rego Devilla (International Journal of Studies in International Education, 2025)
This study explores the impact of pedagogical, personality, social, and professional competencies on students' interest in Social Studies learning in Grade V at SD Inpres Bukkangraki, Bajeng District. Using a quantitative method with total sampling of 28 students, data were obtained via questionnaires and analyzed through multiple regression using SPSS 26. The study confirms that all four competencies have a significant and positive effect on students’ learning interest, both partially and simultaneously. Among these, pedagogical competence has the most dominant effect, emphasizing the importance of teaching strategies in cultivating student interest.